Community-based Sustainable Development Management Model in Vietnam - Experience from the Village Self-governance Model of Vietnamese People in History - Anh Tuyet, Dang Thi; Quyen, Hoang Thi (VNU Journal of Science: Policy and Management Studies; Vol 36 No 2DO - 10.25073/2588-1116/vnupam.4233, 2020)
Along with the economic growth and development, people are facing challenges such as: the exhaustion of non-renewable resources, the natural environment is seriously destroyed, ecological balance is broken. Ensuring basic human rights is difficult because economic growth is not always accompanied by social progress and justice. Therefore, since the 1980s, "sustainable development" has become a strategy, that is mentioned by many countries and international organizations. Sustainable development is a relatively broad concept that covers all aspects and aspects of life, so sustainable development management requires the participation of many actors from state management institutions. to non-state institutions. This article focuses on answering two main questions: 1) Why is it necessary to build a community-based sustainable development management model? 2) What values can we inherit and promote from the Vietnamese tradition of self-governance in building community-based sustainable development management models in the current context?